MEROPS: the database of proteolytic enzymes, their substrates and inhibitors - Rawlings, Neil D. (Oxford University Press, 2012)
Peptidases, their substrates and inhibitors are of great relevance to biology, medicine and biotechnology. The MEROPS database (http://merops.sanger.ac.uk) aims to fulfil the need for an integrated source of information about these. The database has hierarchical classifications in which homologous sets of peptidases and protein inhibitors are grouped into protein species, which are grouped into families, which are in turn grouped into clans. The database has been expanded to include proteolytic enzymes other than peptidases. Special identifiers for peptidases from a variety of model organisms have been established so that orthologues can be detected in other species. A table of predicted active-site residue and metal ligand positions and the residue ranges of the peptidase domains in orthologues has been added to each peptidase summary. New displays of tertiary structures, which can be rotated or have the surfaces displayed, have been added to the structure pages. New indexes for gene names and peptidase substrates have been made available. Among the enhancements to existing features are the inclusion of small-molecule inhibitors in the tables of peptidase–inhibitor interactions, a table of known cleavage sites for each protein substrate, and tables showing the substrate-binding preferences of peptidases derived from combinatorial peptide substrate libraries.